Emittance measurement of electron beam of RF gun with plasma ferroelectric cathode - Khodak, I.V.; Kushnir, V.A. (Вопросы атомной науки и техники, 2006)
An RF gun with a plasma ferroelectric cathode can generate intense electron beams with peak current in a bunch
up to 10² A. The space charge forces of the beam increase errors of the beam emittance measurement using a
‘quadrupole’ technique. The errors of the measurements and the implementation of the ‘pepper-pot’ technique are
referred in the paper. Studied is the beam emittance generated by a single-cell S-band RF gun with the plasma
ferroelectric cathode. The beam pulse current is 6 A (current in a bunch is 60 A) with pulse duration 40…90 ns and
particle energy ≅ 500 keV. ВЧ-пушка с плазменным ферроэлектрическим катодом может генерировать интенсивные электронные пучки с током в сгустке до 10² A. Силы пространственного заряда такого пучка увеличивают погрешности измерения эмиттанса с использованием квадруполей. В работе рассмотрены погрешности измерений и реализован ‘pepper-pot’-метод измерения эмиттанса. Был исследован эмиттанс пучка, генерируемого однорезонаторной ВЧ-пушкой S-диапазона с плазменным ферроэлектрическим катодом. Импульсный ток пучка составляет 6 A (ток в сгустке до 60 А) при длительности импульса 40…90 нс и энергии электронов ≅ 500 кэВ. ВЧ-гармата з плазмовим фероелектричним катодом може генерувати інтенсивні електронні пучки зі
струмом у згустку до 10² A. Сили просторового заряду такого пучка завищують погрішності вимірювання
емітансу з використанням квадруполів. В роботі розглянуті погрішності вимірювань та реалізований
‘pepper-pot’-метод вимірювання емітансу. Було досліджено емітанс пучка, що генерується
однорезонаторною ВЧ-гарматою S-діапазону з плазмовим фероелектричним катодом. Імпульсний струм
пучка дорівнює 6 A (струм в згустку до 60 А) при тривалості імпульсу 40…90 нс та енергії електронів
≅ 500 кеВ.